2012
DOI: 10.1136/bcr-2012-007178
|View full text |Cite
|
Sign up to set email alerts
|

Oral squamous cell carcinoma associated with myiasis

Abstract: SummaryMyiasis is a general term for infection by fly larvae feeding on the host's necrotic or living tissue. Although infestation by fly larvae is much more prevalent in animals, it is a relatively frequent in occurrence. Oral myiasis is a rare pathology in humans and is associated with poor oral hygiene. Larvae cause itching and irritation due to their crawling movements and can destroy vital tissues, inducing serious or even life-threatening haemorrhage. The treatment is a mechanical removal of the maggots … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 8 publications
1
43
0
Order By: Relevance
“…Although this is not a lethal disorder, in older adults, the systemic status is essential for a good prognosis. This case and other similar studies showed successful treatment . However, some cases in older adults with immunocompromised status (anemia, dehydration, low weight), stroke, tube feeding, cancer lesions, or trauma reported the patients died, as a result of these secondary causes, i.e., pneumonia, respiratory failure, and sepsis …”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Although this is not a lethal disorder, in older adults, the systemic status is essential for a good prognosis. This case and other similar studies showed successful treatment . However, some cases in older adults with immunocompromised status (anemia, dehydration, low weight), stroke, tube feeding, cancer lesions, or trauma reported the patients died, as a result of these secondary causes, i.e., pneumonia, respiratory failure, and sepsis …”
Section: Discussionsupporting
confidence: 61%
“…Debridement has a curative function, but some foreign body reactions may occur in cases in which maggots remain in the surgical wound due to incomplete debridement . Certain drugs are suggested as adjuvants to treatment, such as Ivermectin (10 cases, and this study) and Nitrofurazone . Other chemical agents also were used to encourage the maggots to exit the wound through induction of tissue hypoxia or mechanical action of the irrigation, concomitantly, such as saline, chloroform, turpentine oil, hydrogen peroxide, and chlorhexidine .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, mechanical removal is not sufficient treatment because of the larva's hooks that it uses to grip the tissue cavity (Verma, Marya, 2011;Dharshiyani et al, 2012). Application of ether to the wound has been suggested in order to compel the maggots wiggle out of the host tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The wounds can be debrided by irrigating with normal saline or antiseptic medicaments such as 0.2% aqueous chlorhexidine, iodoform, ethyl chloride, mercuric chloride, creosote or turpentine oil. Whitehead varnish pack, which contains ether, can be applied to the raw wound for protection during the healing phase 3 (Dharshiyani et al, 2012). Recently, Ivermectin, a semisynthetic macrolide antibiotic used in veterinary medicine, has been applied to the treatment of oral myiasis.…”
Section: Discussionmentioning
confidence: 99%